An experimental analysis on cross-asset arbitrage opportunity and the law of one price - Jieyi Duan; Nobuyuki Hanaki (Osaka University, Institute of Social and Economic Research (ISER), 2024)
This study experimentally investigates the impact of the lack of arbitrage opportunities across different assets on the realization of the law of one price. Our experiment is based on the framework established by Charness and Neugebauer (2019) where participants, acting as traders, are involved in transactions with two different types of assets. An increase in the magnitude of price discrepancies and fundamental mispricing are observed when traders are unable to engage in arbitrage between different assets. The presence of opportunities for cross-asset arbitrage typically prompts traders to pay closer attention to the pricing of an alternative asset during transactions, which effectively reduces the extent of price discrepancies and mispricing.
Keywords: C90; D84; 330; The law of one price; Arbitrage opportunities across different assets; Price discrepancy; Asset Pricing